Analisis Reaksi Pasar Modal Perusahaan LQ45 Terhadap Pergerakan Nilai Tukar di Masa Pandemi Covid 19 - Hastina Febriaty; Andryan Septian (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
COVID-19 is one of the major pandemic disasters that really has a snowball effect and simultaneous effects on all aspects of life. One of those affected by this pandemic is the occurrence of a fairly deep exchange rate movement in 2020. The purpose of this study is to analyze how the capital market reacts to LQ45 companies with an approach to IHSGLQ45 on the movement of the Rupiah exchange rate against the dollar by using quantitative data that presented in the form of time series data. The data used are companies listed on LQ45 on the Indonesia Stock Exchange, namely in the period April 2020 to July 2021. The results of this study indicate that during this pandemic the depreciation of the rupiah against the dollar that occurred running into the capital market occurred due to companies that had going public on the IDX, most of them have foreign debt in the form of foreign currency (forex). In addition, going public produces products that use a lot of imported materials. This depreciation of the exchange rate resulted in an increase in the amount of company debt and production costs incurred in rupiah currency and in the end would lead to a declining company profitability.